2011
DOI: 10.2135/cropsci2010.10.0581
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Germplasm Resistant to Sheath Blight from the USDA Rice Core Collection

Abstract: Sheafh blight, oaused by the fungal pathogen Rhizoctonia solani, is one of the most important and widely distributed diseases capable of infesting numerous orops including rioe {Oryza sativa L.). Resistant germplasm with wide variation is essential for controlling this disease via breeding efforts, and genetic background helps design breeding strategies. We used the microchamber method to evaluate the USDA rice core collection, including 1794 accessions from 114 countries, for sheath blight resistance. Seventy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Table 2 shows that the panicle-related traits, straighthead susceptibility and blast resistance frequently appeared across all sets. This may be related to previous knowledge that the variations in panicle characteristics, straighthead susceptibility and blast resistance are strongly associated with the indica and japonica differentiation: panicles are long and sparse in indica but short and dense in japonica (Bai et al, 2016); straighthead resistance and blast resistance are greater in indica than japonica (Yan et al, 2005; Jia et al, 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Table 2 shows that the panicle-related traits, straighthead susceptibility and blast resistance frequently appeared across all sets. This may be related to previous knowledge that the variations in panicle characteristics, straighthead susceptibility and blast resistance are strongly associated with the indica and japonica differentiation: panicles are long and sparse in indica but short and dense in japonica (Bai et al, 2016); straighthead resistance and blast resistance are greater in indica than japonica (Yan et al, 2005; Jia et al, 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Most R genes in plants that have been cloned to date encode NBS-LRR proteins, and these large and abundant proteins are involved in the detection of diverse pathogens, including bacteria, fungi, viruses, nematodes, insects, and oomycetes (Meyers et al 2003;Belkhadir et al 2004). Many studies have shown pathogen differentiation in genetic structure and geographic distribution in rice (O. sativa) (Shang et al 2009;Jia et al 2011Jia et al , 2012, wheat (Triticum aestivum) (Stukenbrock et al 2006), barley (Hordeum uhulgare) (Zhang et al 1987), and banana (Musa ×paradisiaca) (Carlier et al 1996).…”
Section: Rga Markers Reveal Genetic Differentiation Of Resistant Genesmentioning
confidence: 99%
“…Similarly, the resistant alleles to sheath blight in IND and AUS are greater than in ARO, TEJ, and TRJ. Jia et al (2011) reported most germplasms resistant to sheath blight derived from Southern Asia (31%), followed by China (29%), Africa (15%), South America (13%), Central America (4%), Oceania (4%), and the North Pacific (2%).…”
Section: Rga Markers Reveal Genetic Differentiation Of Resistant Genesmentioning
confidence: 99%
“…The highest AUC obtained by the LRM accounts for 0.9977 (Table 1) Importantly, the panicle-related traits, straighthead susceptibility and blast resistance frequently appeared across all sets. These findings may be related to previous knowledge that the variability in panicle characteristics, straighthead susceptibility and blast resistance is strongly associated with the indica and japonica classification; panicles are long and sparse in indica but short and dense in japonica (Bai et al, 2016); straighthead resistance and blast resistance are greater in indica than japonica (Yan et al, 2005;Jia et al, 2011). Though I have presented only the best selection of predictors in each set, other selections of predictors producing a certain AUC level or greater (e.g.…”
Section: Discussionmentioning
confidence: 71%